Brazilin Ameliorates High Glucose-Induced Vascular Inflammation via Inhibiting ROS and CAMs Production in Human Umbilical Vein Endothelial Cells. (1st March 2014) - Jayakumar, Thanasekaran; Chang, Chao-Chien; Lin, Shoei-Loong; Huang, Yung-Kai; Hu, Chien-Ming; Elizebeth, Antoinet Ramola; Lin, Shih-Chang; Choy, Cheuk-sing
Abstract : Vascular inflammatory process has been suggested to play a key role in the initiation and progression of atherosclerosis, a major complication of diabetes mellitus. Recent studies have shown that brazilin exhibits antihepatotoxic, antiplatelet, cancer preventive, or anti-inflammatory properties. Thus, we investigated whether brazilin suppresses vascular inflammatory process induced by high glucose (HG) in cultured human umbilical vein endothelial cells (HUVEC). HG induced nitrite production, lipid peroxidation, and intracellular reactive oxygen species formation in HUVEC cells, which was reversed by brazilin. Western blot analysis revealed that brazilin markedly inhibited HG-induced phosphorylation of endothelial nitric oxide synthase. Besides, we investigated the effects of brazilin on the MAPK signal transduction pathway because MAPK families are associated with vascular inflammation under stress. Brazilin blocked HG-induced phosphorylation of extracellular signal-regulated kinase and transcription factor NF- κ B. Furthermore, brazilin concentration-dependently attenuated cell adhesion molecules (ICAM-1 and VCAM-1) expression induced by various concentrations of HG in HUVEC. Taken together, the present data suggested that brazilin could suppress high glucose-induced vascular inflammatory process, which may be closely related with the inhibition of oxidative stress, CAMs expression, and NF- κ B activation in HUVEC. Our findings may highlight a new therapeutic intervention for the prevention of vascular diseases.